Vertebral bone marrow fat is independently associated to VAT but not to SAT: KORA FF4 - whole-body MR imaging in a population-based cohort - Hasic, Dunja; Lorbeer, Roberto; Bertheau, Robert; Machann, Jürgen; Rospleszcz, Susanne; Nattenmüller, Johanna; Rathmann, Wolfgang; Peters, Annette; Bamberg, Fabian; Schlett, Christopher L. (Nutrients, 2020)
The objective of the current study was to assess the relationship of bone marrow adipose tissue (BMAT) content to abdominal fat depots, including visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT), as well as cardiovascular risk factors (CVRF) beyond physical activity in a population-based cohort study undergoing whole-body magnetic resonance (MR) imaging. Subjects of the Cooperative Health Research in the Augsburg Region (KORA) FF4 study without known cardiovascular disease underwent fat fraction quantification in vertebrae (BMATL1/L2) via a 2-point T1-weighted volumetric interpolated breath-hold examination (VIBE) Dixon sequence. The same MR sequence was applied to quantify VAT and SAT volume. Subjects' characteristics, including physical activity, were determined through standardized exams and self-assessment questionnaires. Univariate and multivariate linear regression were applied. In the cohort of 378 subjects (56 ± 9.1years; 42.1% female), BMATL1/L2 was 54.3 ± 10.1%, VAT was 4.54 ± 2.71 L, and SAT was 8.10 ± 3.68 L. VAT differed significantly across BMATL1/L2 tertiles (3.60 ± 2.76 vs. 4.92 ± 2.66 vs. 5.11 ± 2.48; p < 0.001), there was no significant differences for SAT (p = 0.39). In the fully adjusted model, VAT remained positively associated with BMATL1/L2 (β = 0.53, p = 0.03). Furthermore, BMATL1/L2 was associated with age (β = 5.40 per 10-years, p < 0.001), hemoglobin A1c (HbA1c; β = 1.55 per 1%, p = 0.04), lipids (β = 0.20 per 10 mg/dL triglycerides; β = 0.40 per 10 mg/dL low-density lipoprotein (LDL); β =-3.21 lipid-lowering medication; all p < 0.05), and less physical activity (β = 3.7 "no or nearly no exercise" as compared to "≥2 h per week, regularly", p = 0.003); gender was not significantly different (p = 0.57). In the population-based cohort, VAT but not SAT were associated with higher BMATL1/L2 independently of physical activity and other cardiovascular risk factors. Further, BMATL1/L2 increased with older age, less physical activity, higher HbA1c, and increased lipids but decreased with lipid-lowering medication.
Gesehen am 21.08.2020